An angle-sensitive detection system for scattered heavy ions - Ganz, R.; Thee, P; Bär, R.; Bethge, K.; Bokemeyer, H.; Folger, H.; Samek, M.; Salabura, P.; Schwalm, Dirk; Stiebing, K. E. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 1999)
A compact detection system for heavy ions scattered in collisions at the Coulomb barrier is presented. This system, consisting of four identical, low-pressure Parallel Plate Avalanche Counter (PPAC) modules with two sensitive layers each, was built to operate in an ultra-high-vacuum environment inside the EPoS II solenoid spectrometer at GSI Darmstadt. The detector covers polar angles between 20° and 70° with respect to the beam axis, and about 80% of 2π in azimuthal angle. Segmented cathodes and a delay-line read-out allow for a determination of both angles with a precision of δΘ≈0.7° in polar and δΦ≈1.5° in azimuthal angle, respectively. The system has been proven to be capable of handling instantaneous rates of up to 5×105 detected ions per second per module. It neither exhibits the degradation of detection efficiency nor loss in resolution over a 500 h period of a 6 MeV/u238U+181Ta measurement at average luminosities of 8×1027cm−2s−1.